PREVALENSI INFEKSI TELUR CACING NEMATODA PADA FESES SAPI POTONG (Bos sp) DENGAN METODE WHITLOCK - Supiana Dian Nurtjahyani; Devi Shintya Agustin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Parasitic nematodes disease is one of impediment to the increasing rate of population and livestock production. Infection prevalence study of egg-worm parasitic nematodes established using 91 samples of cattle feces on February 11th, 2014 at Napis village, Bojonegoro. Feces examination was performed at Parasitology Laboratory , Animal Health Laboratory Unit-Animal Husbandry Department of East Java Province in Tuban by Whitlock method. Observed parameters include the type and infection prevalence of egg-worm parasitic nematodes that was infect, the data obtained were analyzed descriptively. The result showed 42 (46,15 %) of the total sample was single infection by one type of nematodes egg-worm. Worms that infect were Strongyle sp. 35 (38,46 %), Trichuris sp. 2 (2,19%) and Nematodirus sp and Strongyle sp  1 (1.09 %), Strongyle sp and Trichuris sp 4 (4,39%)The conclusion of this study is the prevalence of the highest infection of egg-worm parasitic nematodes as much as 38,46 % by Strongyle sp.and lowest prevalence as much as 1.09 % by Nematodirus sp and Strongyle sp. Key words : Infection prevalence, cattle, nematodes egg-worm, Whitlock